2011
DOI: 10.1089/ten.tea.2010.0700
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fibroblasts in Self-Assembled Skeletal Muscle

Abstract: Small facial skeletal muscles often have no autologous donor source to effect surgical reconstruction. Autologously derived muscles could be engineered for replacement tissue, but must be vascularized and innervated to be functional. As a critical step, engineered muscle must mimic the morphology, protein and gene expression, and function of native muscle. This study utilized a self-assembly process to engineer three-dimensional (3D) muscle from a statically strained muscle cell monolayer. Primary mouse myobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…This hypothesis is supported by the inherent regenerative capacity of skeletal muscle conferred by satellite cells 9,1113 ; the observed inverse relationship between muscle wound size and vascularization/degree of wound healing; and the fact that extracellular matrix proteins synthesized by our constructs are present in the satellite cell microenvironment and implicated in their activation 9,10,13,14 .…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This hypothesis is supported by the inherent regenerative capacity of skeletal muscle conferred by satellite cells 9,1113 ; the observed inverse relationship between muscle wound size and vascularization/degree of wound healing; and the fact that extracellular matrix proteins synthesized by our constructs are present in the satellite cell microenvironment and implicated in their activation 9,10,13,14 .…”
Section: Introductionmentioning
confidence: 54%
“…Arranged into bundles of multinucleated myofibers, skeletal muscle has an inherent regenerative capacity due to the presence of resident mononuclear stem cells, called satellite cells. Satellite cells reside between the basal lamina – a region rich in laminin 9,10 – and the sarcolemma (myofiber plasma membrane) 11 . In addition to a role in regulating muscle turnover during homeostasis, activated satellite cells have been shown to be required for restoration of skeletal muscle tissue function following injury 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts help stabilize engineered muscle tissue and produce important ECM. 35 While Duisters et al reported that levels of miR-133 were 15-fold greater in rat cardiac myocytes compared to rat fibroblasts, 36 the passive force in skeletal muscle myobundles was not sensitive to the anti-miR treatment (Fig. 5B) and transfection of fibroblasts with the anti-miRs did not affect compaction of bundles prepared only with fibroblasts.…”
Section: Discussionmentioning
confidence: 84%
“…The first reported mouse constructs were created using the myoid technique and resulted in greater force production than rat MPCs (19.2 vs. 2.9 kN/m 2 ) [Dennis et al, 2001]. Using fibrin casting, Li et al [2011] showed that coculture with mouse embryonic fibroblasts was required for more complete remodeling and degradation of fibrin, suggesting that mouse myoblasts show a decreased ability to remodel and secrete sufficient ECM. In contrast to Li et al [2011] [Lee and Vandenburgh, 2013], approximately 3 orders of magnitude higher than we have reported in fibrin/Matrigel hydrogels.…”
Section: Mouse Cellsmentioning
confidence: 99%
“…Using fibrin casting, Li et al [2011] showed that coculture with mouse embryonic fibroblasts was required for more complete remodeling and degradation of fibrin, suggesting that mouse myoblasts show a decreased ability to remodel and secrete sufficient ECM. In contrast to Li et al [2011] [Lee and Vandenburgh, 2013], approximately 3 orders of magnitude higher than we have reported in fibrin/Matrigel hydrogels. However, when engineering muscle from the same cell isolation using collagen/Matrigel and fibrin/ Matrigel hydrogels, we have found that fibrin/Matrigel constructs produce approximately 5 times higher force ( table 1 ).…”
Section: Mouse Cellsmentioning
confidence: 99%